Comparison of pre‐ and post‐transplant sun‐safe behavior of kidney transplant recipients: What is needed to improve?. Issue 5 (6th April 2018) - Gellén, Emese; Papp, Bence G.; Janka, Eszter A.; Gáll, Tibor; Paragh, György; Emri, Gabriella; Nemes, Balázs; Remenyik, Éva
Summary: Background: The role of sun exposure in the development of melanoma and nonmelanoma skin cancers is known; however, there are limited data on the contribution of pretransplantation total sun burden (TSB) to the increased skin cancer risk in organ transplant recipients (OTRs). The importance of patient education about sun‐safe behaviors is understood, but educations are often unsuccessful in OTRs. Methods: A questionnaire‐based cross‐sectional study was performed with kidney transplant patients at a single academic center to assess the pre‐ and post‐transplant sun exposure, sun protection habits, and skin cancers. Results: Two hundred and twenty‐one patients participated in the study. 13.1% developed at least one skin cancer. High total sun burden before transplantation was reported by 58.4%, and 65.2% reported education about increased skin cancer risk at the time of transplantation. However, that education did not lead to less sun exposure or better sun protection methods after transplantation. Overall, OTR related but not sun protection‐guided lifestyle changes affecting OTRs after transplantation led to reduction in sun exposure. Conclusion: Our findings highlight the need for more tailored, population‐specific education programmes, even for patients who expect to receive a transplant in the future, and suggest the importance of pretransplantation TSB in determining the post‐transplant skin cancer risk.